2015
DOI: 10.1080/15384101.2015.1007781
|View full text |Cite
|
Sign up to set email alerts
|

A delay prior to mitotic entry triggers caspase 8-dependent cell death in p53-deficient Hela and HCT-116 cells

Abstract: Stathmin/Oncoprotein 18, a microtubule destabilizing protein, is required for survival of p53-deficient cells. Stathmin-depleted cells are slower to enter mitosis, but whether delayed mitotic entry triggers cell death or whether stathmin has a separate pro-survival function was unknown. To test these possibilities, we abrogated the cell cycle delay by inhibiting Wee1 in synchronized, stathmin-depleted cells and found that apoptosis was reduced to control levels. Synchronized cells treated with a 4 hour pulse o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…As a positive control for immunoblots and to test antibody specificity, lysates were prepared from the human Hela cell line as described previously [66]. Where noted, Hela cells were incubated for 24 h in either Brefeldin A (BFA; 3.6 μM; Sigma-Aldrich) or tunicamycin (TM; 2 μg/ml; Sigma-Aldrich) to induce ER stress prior to lysate preparation [45].…”
Section: Methodsmentioning
confidence: 99%
“…As a positive control for immunoblots and to test antibody specificity, lysates were prepared from the human Hela cell line as described previously [66]. Where noted, Hela cells were incubated for 24 h in either Brefeldin A (BFA; 3.6 μM; Sigma-Aldrich) or tunicamycin (TM; 2 μg/ml; Sigma-Aldrich) to induce ER stress prior to lysate preparation [45].…”
Section: Methodsmentioning
confidence: 99%
“…We were unable to detect increased phosphorylated (active) JNK in stathmin-depleted cells by western blots. It is possible that increased active JNK occurs asynchronously in a population of cells, much like the asynchrony in the onset of cell death [12], and, therefore, is undetectable by western blots from cell populations. In order to assess JNK activity in individual cells over time, we used a fluorescently tagged JNK kinase translocation reporter (KTR), a localization-based biosensor of JNK kinase activity [2].…”
Section: Indirect Immunofluorescence and Microscopymentioning
confidence: 99%
“…In the absence of stathmin and loss of a negative feedback loop, active JNK levels should rise and eventually activate apoptosis. HeLa cells are a convenient model system to test this hypothesis since they are easily transfected, and previous studies demonstrated that stathmin depletion induces apoptosis in these cells[7] [6][12]. Using a specific JNK inhibitor or siRNA knockdown to abolish JNK activity, we addressed whether JNK is necessary for induction of cell death in stathmin-depleted cells.…”
mentioning
confidence: 99%
“…101 Corroborating these observations, STMN1 inhibition in cancer cells harboring TP53 mutation has decreased cell proliferation and viability, increased apoptosis and suppressed tumorigenicity, suggesting that STMN1 is required for the survival of p53--mutant cells. [102][103][104][105] Recently, it was suggested that overexpressed STMN1 interacts with p53 and contributes to the gain-of-function of p53. 105 Altogether, these data suggest that targeting STMN1 may be an interesting approach to treat different types of cancers with aberrant p53 function.…”
mentioning
confidence: 99%